2023
DOI: 10.3389/fonc.2023.1091329
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on older cancer patients: Proposed solution by the International Geriatric Radiotherapy Group

Abstract: Older cancer patients are disproportionally affected by the Coronavirus 19 (COVID-19) pandemic. A higher rate of death among the elderly and the potential for long-term disability have led to fear of contracting the virus in these patients. This fear can, paradoxically, cause delay in diagnosis and treatment that may lead to a poor outcome that could have been prevented. Thus, physicians should devise a policy that both supports the needs of older patients during cancer treatment, and serves to help them overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…A significant increase in the level of fear and anxiety in patients undergoing radiotherapy during the COVID-19 pandemic compared to 2016 was confirmed and assessed on the basis of the QAFRT questionnaire and Zung's and Beck's scales. The radiotherapy environment, different treatment regimes, concern about potential complications, and the outcome of treatment during emergency medical situations greatly affect the patient's quality of life [19,20]. The application of new, significantly more complex therapeutic modalities increases the retention of patients in radiotherapy centers.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in the level of fear and anxiety in patients undergoing radiotherapy during the COVID-19 pandemic compared to 2016 was confirmed and assessed on the basis of the QAFRT questionnaire and Zung's and Beck's scales. The radiotherapy environment, different treatment regimes, concern about potential complications, and the outcome of treatment during emergency medical situations greatly affect the patient's quality of life [19,20]. The application of new, significantly more complex therapeutic modalities increases the retention of patients in radiotherapy centers.…”
Section: Discussionmentioning
confidence: 99%
“…A similar systemic review of older head-and-neck-cancer patients undergoing hypofractionated radiotherapy demonstrated that this radiotherapy technique is well tolerated in this patient population with good local control [74]. In the era of the COVID-19 pandemic, hypofractionated radiotherapy also limits the exposure of this vulnerable population to the virus [75]. Thus, any treatment schedules ranging from daily to one or bi-weekly could be tailored to patients' needs depending on the patient's frailty status, mobility, and home distance from the cancer center.…”
Section: Tolerance Of Older Patients With Cutaneous Squamous-cell Car...mentioning
confidence: 99%
“…Older adults preferred telemedicine for basic health concerns; however, face to face visits were preferred for physical exams and more serious/complex issues including hearing bad news [27 ▪ ,28]. Telemedicine is a form of communication that can be instrumental in symptom management for patients with cancer including managing pain, nausea, and vomiting [4]. Telemedicine can also be used for goals of care discussion using a virtual platform.…”
Section: Telemedicine Modes Of Communicationmentioning
confidence: 99%
“…This risk was heightened for individuals over the age of 65 with pre-existing specific illnesses, such as coronary artery disease, obesity, and cancer which were more susceptible to infection, hospitalization, mortality, or other risk factors which make older adults vulnerable to COVID-19 including decreased immunity and frailty [3 ▪ ]. Disruption in the care of chronic diseases caused by the pandemic had the potential to negatively impact the health and function of older individuals [3 ▪ ,4]. The fear of acquiring COVID-19 caused uncertainty to leave home and seek medical care increasing the risk of older adults with cancer to undertreatment.…”
Section: Introductionmentioning
confidence: 99%